ANALISIS STRUKTUR BALING-BALING KAPAL DENGAN MENGGUNAKAN FINITE ELEMENT METHOD - Abduh Zuhdi (2022)
The propellers on the ship convert the power from the main engine into propulsion so the boat can run on water. The hydrodynamic load acting on the ship's propeller continuously results in the strength of the propeller material to the point of fatigue. In this study, a pressure analysis due to hydrodynamic load was carried out using ANSYS Fluent as input data to analyze fatigue life and find the location of the stress hotspot through Structural ANSYS. The loading was carried out with variations in the inlet speed of 3 m/s, 4 m/s, 5.45 m/s, 6.5 m/s, and 7 m/s. Based on the analysis, the best results are in the copper alloy material with a stress value of 18.41 Pa and a minimum cycle of 3.43x10^8. The stress hotspot is in the root area of the back of the analyzed ship's propeller. After all stress and cycle values are obtained, the estimated age of the ship's propeller material is 32.5 years.